2016
DOI: 10.1155/2016/4234061
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Role and Interdependence of Oxidative Stress and Inflammation in Liver Diseases

Abstract: The crucial roles of oxidative stress and inflammation in the development of hepatic diseases have been unraveled and emphasized for decades. From steatosis to fibrosis, cirrhosis and liver cancer, hepatic oxidative stress, and inflammation are sustained and participated in this pathological progressive process. Notably, increasing evidences showed that oxidative stress and inflammation are tightly related, which are regarded as essential partners that present simultaneously and interact with each other in var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
193
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 274 publications
(201 citation statements)
references
References 190 publications
5
193
0
3
Order By: Relevance
“…Meanwhile, many drugs with the properties of anti-inflammation and anti-oxidant, have been used to relieve ALI (Li et al, 2016). Previous studies have evidenced that T11 has the effects of anti-inflammation and anti-oxidant on LPS-stimulated RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, many drugs with the properties of anti-inflammation and anti-oxidant, have been used to relieve ALI (Li et al, 2016). Previous studies have evidenced that T11 has the effects of anti-inflammation and anti-oxidant on LPS-stimulated RAW264.7 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence demonstrate that severe oxidative stress is present in patients with sepsis, due to overload of reactive oxygen species (ROS) and inadequate anti-oxidative defenses [7]. Oxidative stress is involved in the pathology of sepsis through several different mechanisms, and it is highly associated with inflammation [8]. Oxidative stress directly attacks endothelial cells and affects oxygen consumption, thus promoting organ failure [9].…”
Section: Introductionmentioning
confidence: 99%
“…Since the MDA level is considered an indicator of polyunsaturated fatty acid damage, the decreased MDA level indicated attenuated oxidative damage in liver disease [28,29]. Previous studies showed that the detoxification pathway by the internal anti-oxidative system should be the result of an interacting network of multiple enzymes, with SOD catalyzing the first step and then CAT and GSH-Px removing hydrogen peroxide [30,31]. Although our data indicated that Danshen could increase the expression of SOD in ALD model and improve the activity of GSH-Px in NAFLD model, the overexpression of a single antioxidant enzyme in the liver is not sufficient to activate the internal anti-oxidative enzyme system and reduce the toxicity of superoxide [32].…”
Section: Discussionmentioning
confidence: 99%